Contributing to the ICNP®: validating the term cultural diversity - N Geyer; MD Peu; S Roussouw; J Morudi; E Uys (AOSIS, 2005)
The specific aims of this study were to: • Propose a definition of the term cultural diversity; • Validate the term cultural diversity; and • Submit a term and definition for international utilisation to the International Council of Nurses (ICN) for consideration for inclusion in the ICNP®. Background South Africa was one of four African countries (Botswana, South Africa. Swaziland, and Zimbabwe) funded by the WK Kellogg Foundation to participate in the ICNP® project. South Africa had 2 research groups. One of the research groups identified the term cultural diversity to define. Method This was a qualitative study where a philosophical perspective was used to explore, explain and describe nursing practice. The combined method proposed by the International Council of Nurses (ICN) was utilised to define and validate the term cultural diversity. Findings Validation and literature review provided sufficient support for the defined characteristics and the term was finally defined and submitted to ICN in November 2002 as: CULTURAL DIVERSITY is a type of CULTURE with the specific characteristics: co-existence of different groups, e.g. ethnic, religious, linguistic and other groups each with their own values and belief systems, traditions and different lifestyles. Conclusion The research group was informed in December 2003 of the ICNP® Evaluation Committee recommendation that the term cultural diversity will be included in the ICNP®.